Malokodnoprogramiranje zAPEX-om: Priročnik s praktičnimi primeri (University of Maribor Press, 2024)
Low Code Programming with APEX: How to and Practical Cases. This textbook introduces Oracle Application Express (APEX), a low-code platform for building data-driven web applications. It aims to equip readers with the skills to fully utilize APEX for real-world business challenges. Part I covers the basics of APEX in twelve chapters, including environment setup, database preparation, navigation, data exchange, application creation, report and form management, and team collaboration. Part II presents twelve business cases that provide a comprehensive understanding of application development from a business, data, and user interface perspective. Each case includes business views, problem definitions, use cases, data models, and application interfaces. The textbook is designed for approximately 75 hours of study and is suitable for both experienced developers and beginners. It includes additional material such as exported applications, scripts, data and video tutorials to enhance learning.